Numerical simulation of raceway phenomena in a COREX melter–gasifier - Sun, Junjie; Luo, Zhiguo; Zou, Zongshu (Powder technology, 2015)
The raceway of the COREX melter–gasifier where the interaction between gas phase and particle phase appears to be violent plays an important role in the melting process. In order to describe the behaviors of the particle phase and the gas phase in the raceway, a coupled simulation approach of discrete element method (DEM) and computational fluid dynamics (CFD) is performed at a microscopic level. The particle motion, particle phase volume fraction, velocity vector field of particles, velocity vector field of the gas phase and scalar velocity contours of particles in front of tuyere are calculated by the coupled model. In this work, as a result of considering the multiple particle–gas interaction forces (including drag force, virtual mass force, lift force and pressure gradient force) and a well-balanced computational time step, an almost stable cavity is formed in front of the tuyere, and the particles follow a rotating path in this cavity which can be defined as raceway. The scalar velocity contours of particles show that the particle velocity is greatest in the raceway central area, and it will decrease gradually with increasing distance from the raceway center. Furthermore, the calculation result is consistent with results from a physical experiment. Fig. 9. Scalar velocity contours of particles by numerical approach. [Display omitted] •Simulations of particle (cokes) motion in raceway of COREX melter–gasifier using coupled DEM and CFD•The tendency that particles follow rotating paths in the raceway was obtained by a numerical approach.•The calculation result of simulation is in agreement with physical experiment result.•To promote the development of DEM–CFD coupled model in the field of solid–gas flow